Science in Samin: Reconstructing Indigenous Knowledge of the Samin Community into Chemical Concepts for Contextualized Education - Fiadillah, Maulidia Fara; Sumarni, Woro (Journal of Innovation in Educational and Cultural Research, 2026)
Chemistry is often perceived as abstract and disconnected from students' everyday lives. To address this gap, this study aims to identify indigenous knowledge within the Samin community of Blora Regency, Indonesia, and reconstruct it into formal chemical concepts to support contextualized chemistry education. A descriptive qualitative method was employed using an ethnographic approach, with data collected through interviews, observations, documentation, and literature review. The study focused on four traditional practices: Sambongrejo Samin batik making, Kareman tempeh fermentation, Wedang Cangruk herbal drink preparation, and Etawa goat farming. Each practice reflects chemical principles, including polymers, acid–base reactions, thermochemistry, fermentation, redox reactions, and environmental chemistry. The findings reveal that these cultural activities contain valuable scientific elements that can be integrated into chemistry curricula. The study concludes that reconstructing indigenous knowledge into scientific understanding enhances students' engagement and scientific literacy while promoting cultural appreciation. This research contributes to science education by providing a model for ethnoscience-based instruction, linking local wisdom with modern scientific frameworks, and supporting the development of culturally responsive and sustainable chemistry education.